A Man of Intellectual Integrity: А Philosopher, a Culturologist, a Logician (Solonin Yury Nikiforovich – Scientist of St. Petersburg State University) - Boris Yu. Misonzhnikov; Galina S. Melnik (Гуманитарный вектор)
The 300th anniversary of St. Petersburg (Leningrad) State University (February 2024) is an occasion to remember the wonderful scientists who devoted their entire lives to their beloved university. The article is devoted to the scientific work of the philosopher Yu. N. Solonin, noted for his contribution to the theory of philosophy, cultural studies, and communication studies. Yury Nikiforovich was born on June 5, 1941 in Tbilisi. After graduating in 1966 from the Faculty of Philosophy of Leningrad State University, named after A. A. Zhdanov, majoring in logic, he stayed to work at the university, until 1980 he taught at the Faculty of Philosophy, and in 1980 he became a professor at the Faculty of Journalism and Head of the Foreign Press Department, then Dean of the Faculty of Journalism, and in 1989, having defended his doctoral dissertation “Science as a subject of philosophical analysis”, was elected dean of the Faculty of Philosophy. He was elected to the State Duma as a single candidate from such parties as the Unity Party of Russia, Fatherland, SPS and Yabloko. In 2005 Yu. N. Solonin became a member of the Federation Council of Russia, putting the issues of culture and the development of civil society on a practical plane. The range of scientific interests of Yury Nikiforovich Solonin is practically inexhaustible. He addresses not only the history of philosophy and culture, but also the political and ideological life of Russian society, the role of mass media in its development. A scientist is an excellent organizer of science. In the 1990s he managed to preserve the best traditions and maintain the scientific educational status of philosophy. The famous scientist became vice-president of the Russian Philosophical Society and led the work of the first Russian Philosophical Congress in Russian history in 1997. The tradition of the Days of St. Petersburg Philosophy, conceived by Yury Nikiforovich as a large-scale scientific event, is still alive. As part of the Days, several international and all-Russian representative conferences are held annually in November. Circle of scientific interests of Yu. N. Solonin is practically inexhaustible. He addresses not only the history of philosophy and culture, but also the political and ideological life of Russian society, writes about the role of mass media in its development. A scientist is an excellent organizer of science. In the 1990s he managed to preserve the best traditions and maintain the scientific educational status of philosophy. The famous scientist became vice-president of the Russian Philosophical Society and led the work of the first Russian Philosophical Congress in Russian history in 1997. The significance of this scientific publication is the fact that it contains the philosophical ideas of Solonin, which were ahead of their time in many respects and have not lost their relevance and today can be filled with new meanings.